2020
DOI: 10.1128/aem.01682-20
|View full text |Cite
|
Sign up to set email alerts
|

The Intermediates in Branched-Chain Amino Acid Biosynthesis Are Indispensable for Conidial Germination of the Insect-Pathogenic Fungus Metarhizium robertsii

Abstract: Metarhizium spp. are well-known biocontrol agents used worldwide to control different insect pests. Keto-acid reductoisomerase (ILVC) is a key enzyme for branched-chain amino acid (BCAA) biosynthesis and regulates many physiological activities. However, its functions in insect pathogenic fungi are poorly understood. In this work, we identified MrilvC in M. robertsii and dissected their roles in fungal growth, conidiation, germination, destruxins biosynthesis, environmental stress response and insecticidal viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…Metabolomics analysis of P. digitatum revealed that central carbon and energy metabolism were upregulated during germination of spores (Che et al, 2020). In line with previously reported works on gene expression during spore germination (Luo et al, 2020;Swarge et al, 2020), important cellular metabolic pathways including fatty acid biosynthesis and amino acid biosynthesis showed significant changes in the germinating spores in comparison with dormant spores (Figure 4 and Table 3). In the lipid fraction, there is a decrease in fatty acid synthase and trehalase activity (Table 2).…”
Section: Discussionsupporting
confidence: 85%
“…Metabolomics analysis of P. digitatum revealed that central carbon and energy metabolism were upregulated during germination of spores (Che et al, 2020). In line with previously reported works on gene expression during spore germination (Luo et al, 2020;Swarge et al, 2020), important cellular metabolic pathways including fatty acid biosynthesis and amino acid biosynthesis showed significant changes in the germinating spores in comparison with dormant spores (Figure 4 and Table 3). In the lipid fraction, there is a decrease in fatty acid synthase and trehalase activity (Table 2).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, qRT-PCR showed MrilvC expression sharply increased expression at the stage of conidial germination and infection, which is consistent with the impairment of the full virulence on insects treated with direct injection or cuticle infection in our previous study [ 14 ]. BCAAs account for more than 20% of total protein amino acids and are an important constituent of the amino acid pool in organisms [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…The ilvC-deficient (∆MrilvC), and complemented strains (Comp) were constructed from the wild-type (WT) M. robertsii strain ARSEF 23 (ATCC no. MYA-3075) in our previous report [14]. All strains grown on SDAY (4% glucose, 1% peptone, 1% yeast extract powder, and 1.5% agar, w/v) at 28 • C in the dark.…”
Section: Fungal Strain and Maintenancementioning
confidence: 99%
See 2 more Smart Citations